Considering and interpreting leisure: pastimes, entertainments, hobbies and addictions in the Barcelona of 1900 - Teresa-M. Sala (coord.) (Col·lecció Singularitats, 2013)
In the throes of modernization, the Barcelona of 1900 was buzzing with energy and an unprecedented culture of leisure emerged. The city's residents made full use of their free time, forging relationships with one another through a highly varied range of initiatives and activities, taking advantage of existing opportunities and creating new ones. In addition to the traditional celebration of civic festivals, popular meals and various types of processions, innovative new forms of cultural consumption sprang up to satisfy all tastes and budgets. Numerous cinemas opened, the first amusement parks threw open their gates and new theatres raised their curtains. Thanks to these developments, the vicinity around the avenue Paral·lel became the epicentre of Barcelona nightlife. This book offers a panoply of images of the diversions, entertainments and hobbies of that fascinating era of contrasts, the turn-of-the-century Barcelona of Modernisme.